DURABILITY STUDY ON BRIDGE DECKS WITH POSTTENSIONED AND REINFORCED CONCRETE SLABS (International Journal of Engineering Management Science, 2024)
This study investigates the incidence and severity of scaling and cracking in concrete bridge decks across ten surveyed states. The findings indicate that Maharashtra and Gujarat experience the highest percentages of scaling, while West Bengal shows minimal scaling. Air entrained concrete demonstrates superior resistance to scaling compared to non-air-entrained concrete. Transverse cracking is the most prevalent type of cracking, particularly in older decks and longer spans. Chemical analyses reveal a correlation between higher chloride content and spalling, suggesting increased permeability or higher chloride application. The primary cause of surface spalling is identified as the corrosion of reinforcement due to de-icing chemicals. The study underscores the importance of proper design, construction, and maintenance practices to enhance the durability of bridge decks and suggests that innovations like self-healing concrete and corrosion inhibitors hold promise for future improvements.
Keywords: Concrete bridge decks, scaling, cracking, airentrained concrete, transverse cracking, chloride content, surface spalling, durability, self-healing concrete, corrosion inhibitors